PAJAK REKLAME DAN PENDAPATAN ASLI DAERAH 5 WILAYAH JAKARTA - Annisa Putri Rahmadani; Hurian Kamela (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to analyze the effectiveness level and contribution rate of billboard tax revenue in 2023 based on the Jakarta Governor Regulation (Pergub) No. 12 of 2023 regarding the Second Amendment to Governor Regulation No. 27 of 2014 on the Determination of Billboard Rental Value as the Basis for Billboard Tax Assessment. This regulation was issued as a part of the economic recovery efforts post-COVID-19 pandemic and aims to optimize billboard tax revenue. Various incentives offered in this regulation are expected to boost Jakarta's billboard tax revenue. Previously, in 2022, the Jakarta Provincial Government issued Governor Regulation No. 24 of 2022 concerning the First Amendment to Governor Regulation No. 27 of 2014. However, billboard tax revenue in 2022 fell short of the set target. In response, the Jakarta Provincial Government issued Governor Regulation No. 12 of 2023 to enhance the achievement of the billboard tax revenue target. As a result, the effectiveness level of billboard tax revenue this year reached 107.41%, with a contribution rate of 2.26%.